SCREENING OF CHICKPEA GENOTYPES FOR RESISTANCE OF SCLEROTIUM ROT UNDER ARTIFICIALLY INOCULATED CONDITION - TRIPATHI, B.P. (Annals of Agricultural Research, 2014)
Ninety genotypes of chickpea were screened for resistance to collar rot caused by Sclerotium rolfsii under artificially sick field condition.Chickpea genotype were evaluated under artifically inoculated field conditions for resistance to coolar rot. The data indicate that out of 90 genotypes, none of the genotype was completely free from the disease. However, 3 genotypes viz. PG 9414-7, BG 372 and H-00-256 were moderately resistant, 1 genotypes IPC 98-58 moderately susceptible, 4genotypes i.e. BG 1003, BG 1053, LBEG-7 and RSG 7 were susceptible to disease under higher disease pressure